2016
DOI: 10.21474/ijar01/716
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin as an Early Reliable Diagnostic and Prognostic Marker of Neonatal Sepsis.

Abstract: Background:-Sepsis is a common cause of morbidity and mortality among neonates, and current biomarkers for diagnosis are not adequate. The objective of the study was to assess the diagnostic and prognostic value of presepsin.Methods:-One hundred and twenty neonates were enrolled in the study; 80 cases and 40 controls. Presepsin and CRP levels were measured during 1st, 2nd& 6th days of admission for cases while were measured once for each control.Results:-Initial presepsin levels were significantly higher in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…These results were in accordance with other studies by Sabryetal and Sarode et al39,40 However, Morsy et al found no significant correlation between CRP and CD64 in cases with NS 31…”
Section: Discussionsupporting
confidence: 92%
“…These results were in accordance with other studies by Sabryetal and Sarode et al39,40 However, Morsy et al found no significant correlation between CRP and CD64 in cases with NS 31…”
Section: Discussionsupporting
confidence: 92%
“…27e31 The findings of the present study revealed significant positive correlations between PCT with both hs-CRP and presepsin and also between hsCRP versus presepsin. This was in accordance with Abdollahi et al, 24 Spanuth et al, 26 Maurice et al, 27 and Sabry et al 32 To identify the most suitable serum marker for diagnosis of the neonatal sepsis, there need to be sufficient sensitivity and specificity and detection either in early or late stage of the disease. It is difficult to find a single marker for 3 criteria, so it is advisable to use a combination of inflammatory markers as a part of the diagnostic workup of neonatal sepsis.…”
Section: Studied Biomarkerssupporting
confidence: 86%
“…In this review five articles were not found in the databases we used for our literature search. Out of those five articles, one article was not available in full text [24] and two other articles were not eligible for our review (in one article it was unclear whether they investigated EOS or LOS [25] and in one article unusual ranges of sCD14-ST values were used [26]). Therefore out of this review, two articles [27, 28] were found to be appropriate to use in our review and were included afterwards.…”
Section: Resultsmentioning
confidence: 99%